Vitamin D status is associated with hepcidin and hemoglobin concentrations in patients with severe traumatic injury. Issue 6 (December 2020) - Apple, Camille G.; Miller, Elizabeth S.; Kannan, Kolenkode B.; Stortz, Julie A.; Cox, Michael; Loftus, Tyler J.; Parvataneni, Hari K.; Patrick, Matthew; Hagen, Jennifer E.; Brakenridge, Scott; Efron, Philip A.; Mohr, Alicia M.
Abstract : BACKGROUND: Severe traumatic injury leads to persistent injury-associated anemia that is associated with hypercatecholaminemia, systemic inflammation, increased hepcidin, and a functional iron deficiency. Vitamin D has been shown to reduce proinflammatory cytokines and hepcidin concentrations. This study aimed to investigate the association of vitamin D status with inflammation, iron biomarkers, and anemia following blunt trauma. METHODS: A prospective observational cohort study comparing blunt trauma patients (n = 45) with elective hip replacement patients (n = 22) and healthy controls (n = 8) was performed. Bone marrow ferroportin, transferrin receptor, and erythroferrone expression was measured using quantitative polymerase chain reaction (qPCR). Plasma was assessed for systemic inflammation, erythropoietin (EPO), iron regulation, and vitamin D (25-OH) concentrations using enzyme-linked immunosorbent assay. Hemoglobin was measured on the day of discharge. RESULTS: Compared with hip replacement, trauma patients had higher plasma interleukin-6 (90.1 vs. 3.8 pg/mL), C-reactive protein (6, 223 vs. 2, 612 ng/mL), and hepcidin (79.3 vs. 21.2 ng/mL) concentrations. Trauma patients had lower vitamin D (25-OH) (12.8 vs. 18.1 ng/mL) and iron (23.5 vs. 59.9 μg/mL) levels compared with hip replacement patients. Despite the higher hepcidin EPO levels, bone marrow erythroferrone expression was increased 69% following trauma. CONCLUSION: Following elective hip replacement, patients did have anemia and impaired iron homeostasis without a significant change in inflammatory biomarkers, EPO, and vitamin D status. Vitamin D status did correlate with systemic inflammation, iron dysfunction, and persistent injury-associated anemia following severe blunt trauma. Further research is needed to determine whether supplementation with vitamin D in the trauma population could improve the persistent injury-associated anemia. LEVEL OF EVIDENCE: Prospective study, prognostic, level III.